2019
DOI: 10.1007/s12161-019-01599-0
|View full text |Cite
|
Sign up to set email alerts
|

A Novel and Accurate Method for Moisture Adsorption Isotherm Determination of Sultana Raisins

Abstract: A novel method (dynamic water transfer based water activity analyzer 13 (DWT) method) based on Fick's law of diffusion for the accurate measurement of 14 moisture sorption isotherm (MSI) has been developed, and was compared with 15 saturated salt solutions (SSS) method and dynamic vapor sorption (DVS) method. 16 MSIs at 25°C of sultana raisins obtained by the three methods were analyzed and 17 compared, and four adsorption models (BET, Halsey, GAB, and Peleg) were used to 18 fit the results. The MSI curves obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
(9 reference statements)
0
2
0
1
Order By: Relevance
“…These isotherms define the relationship between the moisture content and the water activity (a w ) of the product, and make it possible to determine the moisture content at which the product presents the greatest stability to degradative processes. Additionally, moisture sorption isotherms allow for the definition of drying conditions, as well as the packaging and storage, for the product [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…These isotherms define the relationship between the moisture content and the water activity (a w ) of the product, and make it possible to determine the moisture content at which the product presents the greatest stability to degradative processes. Additionally, moisture sorption isotherms allow for the definition of drying conditions, as well as the packaging and storage, for the product [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…is low up to 0.8 of a w , and after this value increases until a w = 1. Li et al (2019) found type III moisture adsorption isotherms for Sultana raisin. Bastıoğlu et al (2017) determined for microencapsulated extra virgin olive oil powder type III sorption isotherms, adjusted to the GAB model.…”
Section: /8mentioning
confidence: 95%
“…Em pressões mais altas, a adsorção ocorre devido à condensação capilar nos mesoporos(DO, 1998). Alguns autores obtiveram isotermas com o formato tipo III para pectina (BASU; SHIVHARE; MULEY, 2013), uva sultana(LI et al, 2019), manga (LINK et al, 2018 e mamão(UDOMKUN et al, 2015).As isotermas do tipo V resultam das interações entre a matriz sólida e o material adsorvido semelhantes a que ocorrem em isotermas do tipo III, porém com tamanhos de poros característicos de material poroso(LOWELL; SHIELDS, 1984).…”
unclassified